2006
DOI: 10.1007/bf03021581
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous acetaminophenvs oral ibuprofen in combination with morphine PCIA after Cesarean delivery

Abstract: Purpose:To compare the effects of iv acetaminophen with those of oral ibuprofen with respect to postoperative pain control and morphine requirements in patients receiving morphine patient-controlled iv analgesia (PCIA) after Cesarean delivery.Methods: Forty-five term patients scheduled for Cesarean delivery were randomized to receive acetaminophen 1 g iv every six hours plus oral placebo (group A) or ibuprofen 400 mg po every six hours plus iv placebo (group I); the first dose of study drug was given 30 min pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 23 publications
2
34
0
2
Order By: Relevance
“…The NRS at rest and movement showed a rising trend and was found to be highest at 12 hours and then a declining trend was observed. Somewhat similar observations were made in the study of Alhashemi et al [12] where they found a peak of morphine requirement between 4 -8 hours. The gradual increase in NRS score and rescue analgesia during this time could be explained by the recession of spinal anaesthesia and patients' mobilization.…”
Section: Discussionsupporting
confidence: 83%
“…The NRS at rest and movement showed a rising trend and was found to be highest at 12 hours and then a declining trend was observed. Somewhat similar observations were made in the study of Alhashemi et al [12] where they found a peak of morphine requirement between 4 -8 hours. The gradual increase in NRS score and rescue analgesia during this time could be explained by the recession of spinal anaesthesia and patients' mobilization.…”
Section: Discussionsupporting
confidence: 83%
“…Results of the similar studies did not show any significant difference in the analgesic effect of intravenous acetaminophen and morphine (3)(4)(5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 82%
“…A single-blind emergency department study over patients presenting with renal colic found that intravenous acetaminophen was equally effective as intravenous morphine (3). There are also some other studies showing that intravenous acetaminophen is as effective as intravenous morphine in pain management (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of these factors has not been carefully studied in clinical trials; nevertheless, we suggest that a potential strategy for minimizing PP HTN would be to use alternative postpartum analgesia such as acetaminophen and narcotics. 19,20 Given the rare, but devastating potential consequences of PP HTN, we congratulate Goel et al for highlighting the high prevalence and the need for additional investigation regarding prevention, pathophysiology, and treatment.…”
Section: Postpartum Hypertension 1691mentioning
confidence: 98%